Citizenship and Family: Revisiting Dred Scott - Jennifer M. Chacón (Washington University Journal of Law & Policy, 2008)
This Essay explores the implications of the Dred Scott case for modern questions about family unity as it is affected by U.S. immigration law and policy. Part I elaborates on Dred Scott’s story, illustrating the central role that family unity played in the case. Part II focuses on the arc of history as it extends from Dred Scott to the present, demonstrating that the historical narrative of the Dred Scott case has often been used as a rallying cry for thicker, more robust conceptions of citizenship and for “equal citizenship.” Part III argues that, when it comes to the right to family integrity, a contemporary re-reading of the story of the Dred Scott family and a reexamination of the legacy of the Dred Scott decision might actually favor a decoupling of the right to family integrity and the rights associated with formal citizenship. In lieu of a more robust definition of citizenship that encompasses the right to family integrity, perhaps the Dred Scott case and its aftermath counsel us to move toward a more human-rights centered definition of the right to family integrity, applicable to all persons subject to the jurisdiction of U.S. laws. Part IV concludes that a broader understanding of the right to family would require revisions to certain components of U.S. immigration laws that pose clear, and sometimes unnecessary, barriers to family integrity.
Keywords: Civil rights – Consitutional history; Families; Citizenship; Dred Scott; Dred Scott v. Sandford 60 U.S. (19 How.) 393 (1857); Abolition of slavery; Diversity jurisdiction; Equal protection; United States